2018
DOI: 10.20319/pijss.2018.33.10761091
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Competency Dimensions and Organizational Support in Climate Change Advisory Service Delivery

Abstract: Agricultural sector is vital not only to the livelihood of Malaysian farmers but also to Malaysian economy. However, the sector is currently being threatened by environmental phenomenon in form of climate change. Majority of Malaysian farmers are small-holders who rely mostly on extension workers for information and advisory services. Hence, it is the job of these extension workers to facilitate adaptation among their clientele. This study assessed the factors influencing the performance of such job among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Thus, the training needs related to knowledge of the technological resources available in the personal and professional sphere are of high importance. This study consistent with his study by Umar, et al (2018) noted that high need training in this area and significant at level 0.01 In contrast, integrating ICT with teaching presents a lower level of demand. This result is consistent with the study of Almerich et al (2011), which showed that personal and contextual factors have a complex influence on the structure and relations of computer and ICT use.…”
Section: Skills and Knowledge In Computer And Ictsupporting
confidence: 91%
“…Thus, the training needs related to knowledge of the technological resources available in the personal and professional sphere are of high importance. This study consistent with his study by Umar, et al (2018) noted that high need training in this area and significant at level 0.01 In contrast, integrating ICT with teaching presents a lower level of demand. This result is consistent with the study of Almerich et al (2011), which showed that personal and contextual factors have a complex influence on the structure and relations of computer and ICT use.…”
Section: Skills and Knowledge In Computer And Ictsupporting
confidence: 91%
“…Konsep Boyatziz tentang Theory of Job Performance paling memberikan penjelasan kompleks bahwa kinerja organisasi dipengaruhi oleh individu (pengetahuan, kompetensi, jenjang karier, dan motivasi); lingkungan organisasi (strategi, kepemimpinan, sistem manajemen, iklim kerja) dan beban kerja. Konsep Boyatziz sangat relevan dalam melihat faktor yang mempengaruhi kinerja Divisi Penanganan Pelanggaran (Umar et al, 2018) Nampaknya memang benar bahwa pengaruh anggaran terhadap kinerja organisasi sangat besar. Hal ini sudah dijelaskan oleh (Danang & Santoso, 2020) bahwa tidak saja SDM, namun anggaran juga memiliki peranan dalam menyokong organisasi mencapai tujuannya.…”
Section: B Faktor-faktor Yang Mempengaruhi Kinerja Divisi Penanganan ...unclassified
“…Social and cultural beliefs and practices of people, as manifested in their varied interpretations, experience and response to issues, also influence adaptation to climate change (Yaro, 2013). These social and cultural diversities breed varied and diverse understanding of adaptation across the several groups of people (Umar , Man , Shuaibu, & Saleh, 2018).…”
Section: Social and Cultural Barriersmentioning
confidence: 99%